Ensuring Fish Safety Through Sustainable Aquaculture Practices - Carlino-Costa, Camila [UNESP]; Belo, Marco Antonio de Andrade (MDPI, 2025)
Sustainable aquaculture is increasingly vital to meet global protein demands while ensuring fish product safety and environmental stewardship from a One Health perspective. This review addresses fish hygiene as a comprehensive, multi-stage challenge encompassing water quality management, pathogen control, antimicrobial stewardship, feeding practices, humane slaughter, post-harvest handling, and monitoring systems. We examined current practices and technologies that promote hygienic standards and reduce contamination risks across production cycles. The integration of biosecurity measures and alternative health-promoting agents contributes to disease prevention and reduces reliance on antimicrobials. Responsible drug administration aligned with regulatory frameworks minimizes residues and antimicrobial resistance. Feeding strategies incorporating sustainable and safe ingredients further support fish health and product quality. Critical control points during slaughter and post-harvest processing ensure microbial safety and prolong shelf life. Advanced monitoring and traceability systems enable real-time oversight and enhance food safety assurance. Finally, certification programs and robust regulatory policies are essential to standardize practices and facilitate access to international markets. Collectively, these strategies foster sustainable aquaculture that safeguards public health, maintains ecological integrity, and supports economic viability. This holistic approach positions fish hygiene not as a final quality check, but as an integral, continuously managed component of responsible aquaculture production.